Management of basal cell carcinoma with excision followed by rotation advancement flap - Siregar, Remenda; Puspita, Fitri; Oentari, Widyaningsih; Sari, Ari Karmila (Journal of General - Procedural Dermatology and Venereology Indonesia, 2021)
Background: Basal cell carcinoma (BCC) is the most common malignant skin tumor and is derived from pluripotent cells in the basal layer of the epidermis. One of the BCC management options is surgery followed by a skin flap to close the wound defect. Case Illustration: We present a 43-year-old woman with a major complaint of non-healing sores on the left zygomatic region, close to the medial canthus, with frequent episodes of bleeding and itching since one year before admission. The lesion was excised and followed by histopathological examination, which revealed the BCC diagnosis with tumor-free edges. Closure of the defect with a rotation advancement flap was performed with good results. Discussion: The diagnosis of BCC in this patient was based on history taking, dermatological and histopathological examination. According to the dermatological examination, the patient presented with superficial ulcers with hyperpigmented bases, irregular margins and raised edges, partly covered by crust in the left zygomatic region, consistent with typical clinical manifestation of BCC. Histopathological findings of BCC may vary according to the subtype. However, most cases of BCCs usually have similar histological characteristics. Conclusion: The functional and cosmetic result of BCC following excision and defect closure with rotation advancement flap yielded good results with a shorter healing time.